Research on integration strategies and cultural adaptability of regional cuisines in China’s urban dining environments - Lyu Junfeng (SHS Web of Conferences)
This thesis explores how regional cuisines from various parts of China have successfully integrated into the dining markets of large cities amid urbanization, focusing on their adaptation mechanisms, market challenges, and future development trends. Firstly, through the study of successful cases in major cities such as Beijing, Shanghai, and Guangzhou, the thesis reveals how regional cuisine brands cater to the diverse needs of urban consumers through dish adjustments, restaurant atmosphere design, and brand promotion strategies. Secondly, it analyzes the challenges faced by regional cuisines in highly competitive and saturated urban environments, especially issues like homogenized competition and decreased brand differentiation. To address these challenges, regional cuisine restaurants seek to maintain competitiveness through dish innovation and health-oriented transformations. Finally, the thesis forecasts the future development trends of regional cuisines in urban dining markets, pointing out that health orientation, upscale positioning, digitalization, and policy support will become important drivers for the sustained development of regional cuisines. Through an in-depth analysis of these factors, this study provides a theoretical basis and practical reference for the continuous innovation and development of regional cuisines.